2020
DOI: 10.1055/a-1081-2036
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Relationship Between Gut Microbiota and Polycystic Ovary Syndrome (PCOS): a Review

Abstract: ABSTR AC TPolycystic ovary syndrome (PCOS) is an endocrine and metabolic syndrome (MS) with a complex etiology, and its pathogenesis is not yet clear. In recent years, the correlation between gut microbiota (GM) and metabolic disease has become a hot topic in research, leading to a number of new ideas about the etiology and pathological mechanisms of PCOS. The literature shows that GM can cause insulin resistance, hyperandrogenism, chronic inflammation and metabolic syndrome (obesity, diabetes) and may contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
106
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 126 publications
2
106
0
1
Order By: Relevance
“…Meanwhile, den Besten et al [32] found that SCFA could activate peroxisome proliferator-activated receptor-γ in the liver and muscle, thereby regulating uptake of glucose and oxidation of fatty acid. In addition, the gut microbiota could in uence the insulin sensitivity by SCFA-mediating in ammatory responses [33]. In the present study, the abundance of Megamonas in the patients decreased after BZYQ treatment, which was bene cial for reducing intestinal permeability and maintaining intestinal homeostasis.…”
Section: Discussionsupporting
confidence: 47%
“…Meanwhile, den Besten et al [32] found that SCFA could activate peroxisome proliferator-activated receptor-γ in the liver and muscle, thereby regulating uptake of glucose and oxidation of fatty acid. In addition, the gut microbiota could in uence the insulin sensitivity by SCFA-mediating in ammatory responses [33]. In the present study, the abundance of Megamonas in the patients decreased after BZYQ treatment, which was bene cial for reducing intestinal permeability and maintaining intestinal homeostasis.…”
Section: Discussionsupporting
confidence: 47%
“…The gut microbiota has been implicated to play a critical role in metabolic diseases such as PCOS, and may modulate the secretion of mediators of the brain–gut axis [ 64 ]. However, the research is still in its early stage [ 65 , 66 , 67 , 68 ]. Fibre and microbiome may be a confounding factor in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative regulations have been described, as there are studies hypothesizing an endocrine disruptor effect of isoflavones [ 28 , 29 ]. Some of these microbial strains are responsible for highly important pathways including energy adsorption, lipopolysaccharide, and short-chain-fatty acid metabolization and the bile acid pathways [ 30 , 31 ]. Studies on differences in the strain composition in other diseases already showed the importance of single alterations in strains on the phenotype and differences between healthy and diseased subjects.…”
Section: Introductionmentioning
confidence: 99%